Application of The Concept of Critical Toponymies to Street Name Changes in Bandung, Yogyakarta, and Surabaya - Erikha, Fajar (Paradigma: Jurnal Kajian Budaya, 2021)
From 2017 to 2019, a number of street names were changed in Yogyakarta, Bandung and Surabaya City by each Provincial Government for the purpose of celebrating the reconciliation between the Sundanese (West Java) and the Javanese (Central Java, East Java, and Yogyakarta) after years of dispute due to the infamous Bubat Tragedy which occurred in the 14th century. Some existing street names in Yogyakarta and Surabaya were changed to those associated with Sundanese history, such as Jalan Padjadjaran and Jalan Siliwangi, while some existing street names in Bandung were changed to those associated with Javanese history, such as Jalan Majapahit and Jalan Hayam Wuruk. The author explores this phenomenon using the concept of critical toponymies and examines the connections between naming, place-making, and power underlying such policy. This study found that, although the changes were made with good intentions, in some cases this was actually opposed by several factions within the local community because those changes could obliterate the historical significance and collective memory represented by the previous names. From theoretical perspective, this paper also discussed the successful and unsuccessful changes of street names, as well as their relevance to the current context. In other words, our findings can be taken into consideration in future policy-making process.